Prediccion de la altura de salto vertical importancia del impulso mecanico y de la mas muscular de la extremidades inferiores - Ferragut, C.; Cortadellas, J.; Arteaga, R.; Calbet, J. (European Journal of Human Movement, 2003)
The aim of this study was to find out if it is possible to predict the height of the vertical jump from kinematic, dynamometric and anthropometric variables using a multiple linear regression model. Fifty-three subjects, 21 male and 9 female volleyball players of first National categories (First National League and First League), as well as 23 Physical Education students (12 males and 11 females) participated in this study. First, the height of the flight during the performance of a "squat jump" (SJ) and "countermovement jump" (CMJ) was determined. Then, the maximal isometric strength in the squat position was assessed with the knees bent at 90º, 120º and 140º while the electromyographic activity was simultaneously recorded on the vastus lateralis with surface electrodes. The muscle mass of the lower limbs was obtained by dual-energy X- ray absorptiometry (DEXA). The positive mechanical impulse explained on its own 77% of jumping height variability. Prediction power was increased to 82% by including in the model the percentage of body mass represented by de muscle mass of the lower limbs. The inclusion of the muscle mass of the lower limbs, as a third variable, raised the prediction power to 98% of jumping height variability. The same variables allowed for a similar level of prediction during the squat jumps.